Social Identity, Behavior, and Personality: Evidence from India - Utteeyo Dasgupta; Subha Mani; Smriti Sharma; Saurabh Singhal (Institute of Labor Economics (IZA), 2020)
Hierarchies in social identities have been found to be integrally related to divergences in economic status. In India, caste is one such significant social identity where continued discriminatory practices towards the lower castes have resulted in poor outcomes for them. While there is considerable work on such divergence on many economic outcomes along caste lines, there is no work on behavioral preferences and personality traits that can also be adversely affected by such identity hierarchies, and that are important determinants of educational attainments and labor market performances. We combine rich data from incentivized tasks and surveys conducted among a large sample of university students in a Seemingly Unrelated Regression framework and find that the historically marginalized Scheduled Castes and Scheduled Tribes (SCSTs) and Other Backward Classes (OBCs) fare worse than the upper castes along several dimensions of economic behavior such as competitiveness and confidence and personality traits such as grit, locus of control, and conscientiousness. Further, we find that parental investments only have limited compensatory effects on these gaps. This suggests a need for redesigning the structure of affirmative action policies in India as well as targeting interventions with an aim to improving soft skills among the disadvantaged.
Keywords: I23; C9; C18; J24; O15; 330; behavioral preferences; personality; caste; experiments; India